A guide to use flipped classroom strategy to develop speaking skill for Arabic language learners for non-native speakers the high level - Alayaidi, Wafaa Hafez; Alsubhi, Bayan Nair (Journal of Educational and Psychological Sciences, 2020)
The aim of the current research is to prepare a guide to develop speaking skills for Arabic language learners of non-native speakers with using a flipped classroom strategy, where it included an introduction and the goal of that guide, and profile of the strategy and implementation steps, and also included three of the speaking skills that necessary to teach Arabic language to non-native speakers it is a skill of fluency - and the skill of varying the tone of the voice – and the skill of body language, each skill has its own performance indicator, and the researcher has used the descriptive method, and to achieve this objective the researcher used questionnaire tool for the guide to make sure it is usable, and the sample amounted to (7) specialists in teaching Arabic language and teaching Arabic language to non-native speakers, then the opinions of the arbitrators were statistically treated using percentages and all of them agreed on the validity of that guide with proposed amendments .
Keywords: the flipped classroom; speaking skill; Arabic language learners of non-native speakers; The high level